UJI ANTIBAKTERI BAGIAN MINYAK dan AIR DESTILAT BUNGA KENANGA [Cananga odorata (L.) Hook.F. & Thoms] TERHADAP Staphylococcus epidermidis dan KESETARAANYA PADA TETRASIKLIN HCl - Adhe Septa Ryant Agus; Siti Maimunah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Antibacterial tests have been carried out on the oil and water from the distillation of ylang-ylang flowers [Cananga odorata (L.) Hook.F. & Thoms] on the growth of Staphylococcus epidermidis and equivalence to the Tetracycline HCl. using the agar diffusion method and qualitative identification of chemical contents profiles using thin layer chromatography (TLC). For the oil part, there are seven stains in sequences, namely pink, dark green, brown, green blue, red purple, light green, and dark purple, with Rf being 0.13, 0.17, 0.20, 0.38; 0.45, 0.53, and 0.70. Meanwhile, for the water part, three stains formed, namely brown, red, purple, and dark purple, with Rf values of 0.20, 0.45, and 0.70. The equivalent concentration of oil parts for the test solution for the growth of Staphylococcus epidermidis with the reference Tetracycline HCl was 0.563, 0.724, and 0.857ppm. Meanwhile, the equivalent concentration for the water part was 0.413, 0.390 and 0.368ppm. This analysis found that for the oil part of the test solution, there was a significant difference in the inhibitory power of the growth of Staphylococcus epidermidis. At the same time, there was no significant difference in the water.Â